The effect of eight weeks of shoulder-focused exercises on shoulder strength, range of motion, and performance in female volleyball players with scapular dyskinesis - Golnaz Tajik Ahmadabad; Seyed Kazem Mousavi Sadati; Abdulrasol Daneshjoo; Abdullah F. Alghannam (Retos: Nuevas Tendencias en Educación Física, Deportes y Recreación, 2025)
Introduction: Scapular dyskinesia in female volleyball players, caused by repetitive overhead movements, impairs shoulder function and increases the risk of injury. This study evaluated the effectiveness of a shoulder-focused exercise program in addressing these issues.